Genômica organelar e evolução de Genlisea e Utricularia (lentibulariaceae) - Silva, Saura Rodrigues da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Utricularia e Genlisea são gêneros irmãos de plantas carnívoras da família Lentibulariaceae. Possuem aproximadamente 260 espécies representadas em diversas formas de vida. Para o Brasil foram catalogadas 82 espécies, das quais 27 são consideradas endêmicas. Além de dispor das armadilhas carnívoras mais complexas entre plantas, algumas de suas espécies apresentam os menores genomas e as maiores taxas de mutações entre as angiospermas relatadas até o momento. A respeito de seus genomas organelares, os estudos são pífios. Neste contexto, há a necessidade de se investigar como são os genomas organelares, suas estruturas, seus genes e como se deu a evolução das organelas nos gêneros. Portanto este estudo teve como objetivo, a partir de sequenciamento de nova geração e montagem de genomas, estudar e comparar os genomas organelares de Utricularia e Genlisea. Neste âmbito, foram montados e sequenciados os cloroplastos das espécies Utricularia foliosa, U. reniformis, G. aurea, G. filiformis, G. pygmaea, G. repens e G. tuberosa, e o genoma mitocondrial de U. reniformis. Os resultados obtidos revelaram que possivelmente há relação entre forma de vida e presença de genes ndhs nos gêneros, em razão de que para as espécies terrestres há deleção e “pseudogenização” de genes ndhs, já as espécies aquáticas detêm todo repertório de ndhs intacto. A partir das evidências encontradas, foi possível constatar transferência horizontal de genes, inclusive de genes ndhs, em mitocôndrias.

Utricularia and Genlisea are sister genera in the carnivorous family Lentibulariaceae. There are aprproximately 260 species representing diverse life forms. For Brasil there are 82 species, 27 considered endemic. At the moment, besides having the most complex carnivorous traps between all plants, some of its species have miniature genomes and the highest mutational rates among angiosperms. There are few studies regarding its organellar genome. In this context, it is necessary to investigate how are these organellar genomes, its structure, genes, and how evolutionary forces govern these organelles in the different genera. Therefore, the aim of this study is to study and compare the organellar genomes of Utricularia and Genlisea, using next generation sequencing and genome assembly. In this context, chloroplasts of the species Utricularia foliosa, U. reniformis, Genlisea aurea, G. filiformis, G. pygmaea, G. repens and G. tuberosa, and the mitochondrial genome of U. reniformis were assembled and sequenced. The results show that possibly there is a connection between life form and the presence of ndhs genes in the genera, since for the terrestrial species there are ndhs genes that are deleted and pseudogenization, in contrary to the aquatic species which have all intact ndhs repertoir. Concerning the evidences, it was possible to verify horizontal transfer of ndhs and other genes as there are chloroplasts genes in the mitochondria.
Organellar genomes and evolution of Genlisea and Utricularia (Lentibulariaceae)
Keywords: Lentibulariaceae; Utricularia; Genlisea; genômica; organelas; genoma cloroplastidial; genoma mitocondrial; organellar genomics; phylogenomic